Combinational enhancing effects of formulation and encapsulation on digestive stability and intestinal transport of green tea catechins. (17th February 2016) - Son, Yu-Ra; Chung, Jae-Hwan; Ko, Sanghoon; Shim, Soon-Mi
Abstract : The hypothesis was that green tea catechins (GTCs) formulated with vitamin C and xylitol followed by enteric coating with hydroxypropyl methyl cellulose phthalate (HPMCP) or encapsulated into γ-cyclodextrin (γ-CD) could enhance intestinal absorption of GTCs. Surface morphology and size obtained by SEM were different. Digestive stability of GTCs encapsulated into γ-CD or coated with HPMCP was enhanced up to 65.56% or 57.63%, respectively. When GTCs were formulated, the digestive stability was greater than the one not formulated. Formulated GTCs followed by encapsulation into γ-CD significantly increased intestinal transport. Absorption of GTCs was 2.8%, 9.64%, 11.97%, 8.41% and 14.36% for only GTCs, GTCs encapsulated into γ-CD, formulated GTCs encapsulated into γ-CD, GTCs coated with HPMCP and formulated GTCs coated with HPMCP, respectively. This study suggests that GTCs, formulated with vitamin C and xylitol followed by γ-CD encapsulation or HPMCP enteric coating, provide combinational effect to increase bioavailability of GTCs.